First Day Cover commemorating Victor Grignard - Pheulpin, Jean (1971)
Cachet, semipostal stamp, and postmark feature a portrait of the chemist, François Auguste Victor Grignard. The cachet and stamp also depict the apparatus Grignard used to produce the Grignard reaction, a new method for generating carbon-carbon bonds using magnesium to couple ketones and alkyl halides. The Nobel medal for chemistry is also depicted on the stamp.
Keywords: Grignard, Victor, 1871-1935; France; Chemists; Semipostal stamps; Commemorative postage stamps; Science on postage stamps; Nobel Prize winners; Cachets (Philately); First day covers (Philately); Postmarks